Antibacterial activity, cell toxicity, and mechanical property of ultra-high molecular weight polyethylene/chlorhexidine acetate–montmorillonite nanocomposite. (November 2018) - Zhang, Jun; Feng, Fuling; Han, Bing; Wang, Dawei; Fu, Lei; He, Lei; Zhao, Yue; Mo, Hong; Shen, Jian
Nanocomposites have been extensively used in many fields. Their properties can be improved or enhanced by the components in the nanocomposites. In this study, we reported the antibacterial activity, cell toxicity, and mechanical property of a three-component nanocomposite which consisted of ultra-high molecular weight polyethylene (UHMWPE), chlorhexidine acetate (CA), and montmorillonite (MMT). This nanocomposite (UHMWPE/CA-MMT) maintained good short-term resistance to bacterial adhesion, and its long-term resistance to bacterial adhesion was significantly improved as the interlayer space in montmorillonite prevented effectively the agglomeration and precipitation of chlorhexidine acetate after the intercalation of chlorhexidine acetate into montmorillonite. Also, its cell toxicity was reduced as the interlayer space in montmorillonite inhibited the release rate of chlorhexidine acetate. In addition, the mechanical property of UHMWPE/CA-MMT was improved because of the synergistic optimization of these three components. These findings suggested that this three-component nanocomposite UHMWPE/CA-MMT may be a promising biomaterial.